Personal and Workplace Environmental Factors Associated With Reduced Worker Productivity Among Older Workers With Chronic Knee Pain: A Cross-Sectional Survey. Issue 4 (April 2017) - Agaliotis, Maria; Mackey, Martin G.; Heard, Robert; Jan, Stephen; Fransen, Marlene
Abstract : Objectives: The aim of this study was to explore personal and workplace environmental factors as predictors of reduced worker productivity among older workers with chronic knee pain. Methods: A questionnaire-based survey was conducted among 129 older workers who had participated in a randomized clinical trial evaluating dietary supplements. Multivariable analyses were used to explore predictors of reduced work productivity among older workers with chronic knee pain. Results: The likelihood of presenteeism was higher in those reporting knee pain (≥3/10) or problems with other joints, and lower in those reporting job insecurity. The likelihood of work transitions was higher in people reporting knee pain (≥3/10), a high comorbidity score or low coworker support, and lower in those having an occupation involving sitting more than 30% of the day. Conclusion: Allowing access to sitting and promoting positive affiliations between coworkers are likely to provide an enabling workplace environment for older workers with chronic knee pain.